AGAMA DALAM PERFEKTIF MASYARAKAT MADANI - AL BARRA SARBAINI (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
Religion is often considered to be static because they contain dogmatic doctrines and techings tend to invute discourse context towarrds worldly.as a result lose the historical context of religion, social and culture a society that in fct as adherents. Religion is understood that such criticism form various circles of scientists, philosophers and sociologists. Society is defined by a collection of many small or large individuals bound by a unit , customs, rites or typical law, and live togheter. There are few words in the qur’an using to designate or set of human society. In modern society , individual positions member though still influenced b the family, but rather is determined by the values of the individual.